Cirurgia cardíaca pediátrica - complicações no pós-operatório: Revisão integrativa da literatura - Fernandes, Bélquis (Universidade do Vale do Rio dos Sinos, 2011)
In many pediatric units and children´s hospitals, evaluation and treatment of congenital heart disease constitutes the most common reason for admission. Advances in technology and operative techniques have also led to a progressive decrease in morbidity. However, parallel with these advances is an increasing concern about the complications noted in some survivors of cardiac surgery. The aim of this study was to provide a review of the articles published in Brazil regarding to the post operative complications associated with the cardiac surgery in children with congenital heart disease. Unfortunately, few studies in Brazil have evaluated the postoperative status of children undergoing cardiac surgery and none of them cited or correlated the important role of nursery work in intensive care of these patients. The most commons complications are: atelectasis, pneumonia, failure in ventilatory weaning, cardiac tamponade e renal failure.
Keywords: Cirurgia cardíaca; Complicações pós-cirúrgicas; Crianças; Cardiac surgery; Post operative complications; Children